Activity Space for Online Activities: An Opportunity for Building Resilience in Industry 4.0 Era and Post-Covid-19 Pandemic - Puspita Iredo Bettie; Kurniawan Andri; Marfai Muh Aris (E3S Web of Conferences)
Industry 4.0 era and the Covid-19 pandemic have driven a transformation in online activities, enabling people to engange in various tasks from anywhere, which in turn has altered spatial behavior. This study explored the correlation between the characteristics of online activities and the choice of activity space represented in land use patterns. The study classifies online activities into seven clusters using the SelfOrganizing Mapping (SOM) introduced by Kohonen. The spatial distribution of these clusters is visually represented on a land-use map overlay. The study employs Contingency Coefficient C analysis to assess the correlation between online activity characteristics and space selection. The results of data analysis of online activity actors in Semarang City and Yogyakarta City showed that the online activities were spatially distributed at random. This is supported by a chi-square significance value above 0.05 and a Contingency Coefficient C value around 0.3, indicating no significant correlation between the characteristics of online activities and space choice. These findings suggest that online activities can be conducted anywhere, without specific spatial requirements, thereby reducing physical exposure in urban areas. The reduced physical exposure of an area was one indicator of urban resilience from the physical and environmental aspects.